Global research landscape of microplastics and their impact on earthworm: a bibliometric analysis - Tanushree Moharana; Aliva Patnaik; C. S. K. Mishra; Binayak Prasad Behera; Suryasikha Samal; Rashmi Rekha Samal (Discover Environment, 2024)
Abstract Microplastics (MPs) are generated from diverse categories of plastic debris disposed in open. Its entry into the terrestrial ecosystem could not only impact soil physico-chemical attributes but also endanger the lives of biotas including the earthworms which play significant role in the decomposition of organics and sustaining the nutrient pool. There have been consistent efforts by various workers across the globe to study the impact of MPs on the terrestrial environment and exploring potential mitigation strategies to minimize contamination levels. This review presents a bibliometric analysis of scientific publications on impact of MPs on the earthworms from 2017 to 2023. The primary objective is to discern trends among authors, institutions, and countries contributing to research on MPs, particularly concerning their interaction with earthworms. The analysis reveals a steady escalation in the number of publications up to 2022. The VOS viewer software was utilized for data visualization and cluster analysis, unveiling three clusters highlighting keyword groups associated with "microplastics", "soil", and "earthworms". Notably, "microplastics" and "earthworm" emerged as prominent research hotspots.